Automated classification of group B Streptococcus into different clonal complexes using MALDI-TOF mass spectrometry - Huang, Lianfen; Gao, Kankan; Zhong, Huamin; Xie, Yongqiang; Liang, Bingshao; Ji, Wenjing; Liu, Haiying (Frontiers in Molecular Biosciences, 2024)
Objectives: To evaluate the performance of Matrix-Assisted Laser Desorption/Ionization Time-of Flight Mass Spectra (MALDI-TOF MS) for automated classification of GBS (Group B Streptococcus) into five major CCs(Clone Complexes) during routine GBS identification. Methods: MALDI-TOF MS of 167 GBS strains belonging to five major CCs (CC10, CC12, CC17, CC19, CC23) were grouped into a reference set (n=67) and a validation set (n=100) for the creation and evaluation with GBS CCs subtyping main spectrum (MSP) and MSP-M using MALDI BioTyper and ClinProTools. GBS CCs subtyping MSPs-M was generated by resetting the discriminative peaks of GBS CCs subtyping MSP according to the informative peaks from the optimal classification model of five major CCs and the contribution of each peak to the model created by ClinProTools. Results: The PPV for the GBS CCs subtyping MSP-M was greater than the subtyping MSP for CC10 (99.21% vs 93.65%), but similar for CC12 (79.55% vs 81.06%), CC17 (93.55% vs 94.09%), and CC19 (92.59% vs 95.37%), and lower for CC23 (66.67% vs 83.33%). Conclusion: MALDI-TOF MS could be a promising tool for the automated categorization of GBS into five CCs by both CCs subtyping MSP and MSP-M, GBS CCs subtyping MSP-M is preferred for the accurate prediction of CCs with highly discriminative peaks.